Analysis of Determinants of Income Inequality in the Special Region of Yogyakarta Period 2016-2022 - Himmatul Aliyah, Atsna; Rahmawati, Farida (Jurnal Paradigma Ekonomika, 2024)
Income inequality is a common issue in many countries, making it hard for communities to thrive. This study looks at what factors affect income inequality in the Special Region of Yogyakarta from 2016 to 2022. The data used include education, health, labor, and income per person. The study uses a number-crunching approach called panel data regression analysis with E-views 10. The findings reveal that education, health, labor, and per capita income all play a significant role in income inequality. Education has a positive impact on income inequality, while health and labor have a negative impact. Surprisingly, per capita income doesn't significantly affect income inequality. This means that in the Special Region of Yogyakarta, only education, health, and labor partially determine income inequality. Therefore, local leaders should invest in education and health to improve the quality of their workforce, aiming for more equal incomes in society.